The Swiss Solvency Test and its Market Implications - Eling, Martin; Gatzert, Nadine; Schmeiser, Hato (Geneva Papers on Risk and Insurance-Issues and Practice, 2008)
In this paper, we first discuss the characteristics and major benefits of the Swiss risk-based capital standards for insurance companies (Swiss Solvency Test), introduced in 2006. As the insurance industry is one of the largest institutional investors in Switzerland, changes to its asset and liability management as a result of the new regulatory framework could have striking economic effects. Thus, we further examine significant market implications for the Swiss economy due to possible changes in the asset and liability management of Swiss insurance companies. We investigate resulting effects on the Swiss capital market, focusing on bond, real estate, stock, foreign exchange markets, and the situation in case of a capital market crisis. Furthermore, we analyze potential consequences to corporate financing and product design. Most of the considered consequences result from the transition of past (in principle, not risk-based) supervision to risk-based supervision and can thus be generalized to other supervision systems, in particular Solvency II.
WiSo-Import:2015-03-26:1363
Keywords: Swiss Solvency Test; risk-based supervision; liability management; insurance industry; asset management